A gastro-resistant ovalbumin bi-layered mini-tablet-in-tablet system for the delivery of Lactobacillus acidophilus probiotic to simulated human intestinal and colon conditions. (2nd February 2015) - Govender, Mershen; Choonara, Yahya Essop; van Vuuren, Sandy; Kumar, Pradeep; du Toit, Lisa Claire; Pillay, Viness
Abstract: Objectives: The viability of probiotic bacteria during formulation processes and delivery is vital to ensure health benefits. This study focuses on the use of gastro-resistant denatured ovalbumin for the targeted delivery of probiotic L actobacillus acidophilus to simulated human intestinal and colon conditions through a bi-layered mini-tablet-in-tablet system (BMTTS). Methods: The BMTTS consists of two gastro-resistant ovalbumin mini-tablets containing L . acidophilus suspended in lactose and eudragit S100 for targeted intestinal and colonic delivery respectively. Luminescence has been utilized to ensure probiotic viability during formulation processes in addition to determining all probiotic release profiles. The mechanism of probiotic release from the ovalbumin matrix was ascertained using mathematical modelling and molecular docking studies. Magnetic resonance imaging and differential scanning calorimetry are also included as part of the in-vitro characterization of the ovalbumin system. Key findings: The BMTTS was effective in the delivery of L . acidophilus to simulated human intestinal and colon conditions. Formulation processes were furthermore determined to maintain probiotic viability. Statistical analysis of the release data noted a significant effect of pH denaturation on the release properties of ovalbumin. Magnetic resonance imaging results have indicated a decrease in ovalbumin matrix size upon exposure to simulated intestinal fluid. Molecular docking studies carried out depicted the interaction and binding positions inherent to the ovalbumin–pancreatic trypsin interaction complex indicating the possible enzymatic degradation of ovalbumin leading to the release of the probiotic from the protein matrix. Conclusions: The BMTTS has been determined to be effective in the protection and delivery of probiotic L . acidophilus to simulated human intestinal and colonic conditions. Molecular docking analysis has noted that pancreatin exerts a significant effect on probiotic release from the gastro-resistant ovalbumin matrix.